Sistem Informasi Pengolahan Data Penduduk Berbasis Web Di Griya Asri 2 Desa Sumberjaya Tambun Selatan - Alfan Sahid_; Adie Kusna Wibowo (LPPM STMIK AL MUSLIM, 2024)
The development of website-based information technology has now become a means of business, communication and even assisting in processing important data, especially within government agencies at the RT 05 and RW 24 Housing Griya Asri 2 Desa Sumbejaya Tambun Selatan, currently processing population data still manually, namely using documents that have been exists and is photocopied and recorded in a ledger manually to store data, as in the case of searching for population data, of course it will feel less than optimal and relatively time consuming. However, this is not a good step in overcoming existing problems because officers are still having difficulty finding complete population information. In this regard, this population data processing information system was designed and developed to assist the data management process to make it easier, more efficient and to provide the necessary information as a whole. The research method applied is the Research and Development (R&D) method, with system testing using Black Box Testing based on system functionality. The results showed that the population data processing information system fulfilled the functionality aspect, where the system was designed and developed according to the functions that were running and as expected and there were no errors that occurred in the system. So that the population data processing information system runs well and is in accordance with the requirements needed in managing population data. Keywords: Web-based population system, population application, Php and MySQL, Black Box